2011
DOI: 10.1292/jvms.10-0460
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Butylated Hydroxytoluene on Dog Sperm Longevity in Chilling Storage and Cryopreservation

Abstract: ABSTRACT. This study evaluated the effect of butylated hydroxytoluene (BHT), a lipid-soluble antioxidant, on dog sperm in chilling storage and cryopreservation. In Experiment 1, 0.2, 0.4, 0.8 and 1.6 mM BHT were added to egg yolk Tris extender (EYT), and sperm were stored at 4C for 96 hr. Sperm motility, viability, acrosomal integrity and morphological abnormality in the BHT treatment groups were not different from those of the control (0 mM BHT). In Experiment 2, the effect of BHT in EYT containing 0.75% Equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
3
12
0
2
Order By: Relevance
“…There are many factors which can contribute to the microscopic sperm parameters. In our study, CASA, progressive motilities and viability were influenced by the concentration of BHT as previously reported [51,29,47,24]. However, in our trial, subjective motility, HOST, acrosome integrity, sperm motion characteristics and acrosome reaction status were not influenced by the level of BHT which is in agreement with the findings of Bucak et al [17].…”
Section: Discussionsupporting
confidence: 92%
“…There are many factors which can contribute to the microscopic sperm parameters. In our study, CASA, progressive motilities and viability were influenced by the concentration of BHT as previously reported [51,29,47,24]. However, in our trial, subjective motility, HOST, acrosome integrity, sperm motion characteristics and acrosome reaction status were not influenced by the level of BHT which is in agreement with the findings of Bucak et al [17].…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in accordance with a recent work done, in which BHT at high concentrations of 1.6mM significantly decreased the sperm motility, viability, and acrosomal integrity in canine semen (Sahashi et al, 2011). The damage inflicted on the sperm membrane during cryopreservation renders the membrane more permeable to the BHT metabolites which, in turn, has a harmful effect (Shoae and Zamiri, 2008;Sahashi et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Sahashi et al (2011) have recently reported an optimal inclusion level of 0.4mM BHT in canine semen. The optimal inclusion level for BHT seems to be a species specific characteristics as indicated by previous works for boar (Roca et al, 2004), cattle bull (Shoae and Zamiri, 2008), and buffalo bull (Ijaz et al, 2009) semen recorded as 0.05−2.0, 0.5−1.0, and 1.0−2.0mM, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations